Poesie, Lyrik, Dichtung or Gedichte? - Keywords in Poetic and Metapoetic Writing Tadeusz Różewicz in German Translation - HARTMANN, Bernhard (Transfer. Reception Studies, 2017)
In his poetic and metapoetic writing, Tadeusz Różewicz consciously works with the multiple meanings of the word poezja, which may be translated into German as Poesie, Lyrik, Dichtung, or Gedichte. Based on an analysis of the poezja in Różewicz's poetry, the present paper examines the word's translations into German by Henryk Bereska, Karl Dedecius, Gȕnter Kunert, Peter Lachmann, and Alois Woldan.